Plurality in Buriat and Structurally Constrained Alternatives. (20th December 2019) - Bylinina, Lisa; Podobryaev, Alexander
Abstract: We offer a solution to a puzzle in the number interpretation of nominals in Buriat. Buriat has a two-way number opposition in morphology (unmarked vs. plural), but semantically, both forms may be number neutral. We show that even though the number neutrality of unmarked nominals is heavily restricted, it does not boil down to (pseudo-)incorporation. Our proposal is that unmarked nominals can be either singular (projecting a NumP) or numberless (lacking a NumP). In case they are singular, they are semantically strictly atomic, but when there are numberless they are truly number neutral, just like the plurals. The plurality inferences of plurals and the consistent number neutrality of numberless nouns are accounted for in a Katzirian system with structurally defined alternatives.